(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Stress is a chemical process in the human brain, which generate by some external affectional or forcefully sources. Stress can be relaxed but one can learn how to manage it .In the Jharsuguda District of Odisha state ,within last few years has shown that a large numbers of small scale private Industries has been developed . The majority of Women Workers are engaged in those private sectors.The present study is based on a sample of 70 women employees from various private organizations in Jharsuguda district, the majority of which were experienced more than 2 years. Here the main discussion is, what changes are required to manage stress among working women and what is being done to get the best services in the private sector. For that, a set of questioners are framed for analysis and to prevent the predominant factor that causes stress and to provide the best solutions to overcome it.